Adaption of the structure of carbon nanohybrids toward high-relaxivity for a new MRI contrast agent. Issue 63 (16th June 2016) - Li, Juan; Cui, Rongli; Chang, Yanan; Guo, Xihong; Gu, Weihong; Huang, Huan; Chen, Kui; Lin, Guoming; Dong, Jinquan; Xing, Gengmei; Sun, Baoyun
Abstract : The structure and physicochemical properties of the carbon nanohybrids, rather than the Gd concentration, determined their higher relaxivity. Abstract : Water-soluble GO–Gd@C82 nanohybrids exhibit high relaxivities and could be explored as potential magnetic resonance imaging (MRI) contrast agents. To better understand the relaxation mechanism in the novel carbon nanohybrids, in the present paper, after layers of in-depth analysis and exploration, we propose that the structure and the physicochemical properties of the carbon nanohybrids contribute significantly to the enhanced relaxivity. Better electron transfer from Gd@C82 to the GO nanosheet, appropriate electric conductivity and size of the GO used, an increased number of H proton exchange sites and an adequate concentration of Gd 3+ should result in optimal equilibrium for high relaxivity of the GO–Gd@C82 . These results are important for constructing and optimizing novel nanoscale architectures with higher relaxivity.